ATRIAL FIBRILLATION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - E. I. Leonova; G. G. Shehan; V. S. Zadionchenko; K. M. Bogatyrova (Столичная издательская компания, 2015)
Characteristics of atrial fibrillation pathogenesis in patients with chronic obstructive pulmonary disease are discussed. The impact of chronic obstructive pulmonary disease treatment on the onset and course of atrial fibrillation, as well as approaches to the treatment of atrial fibrillation in this category of patients are also considered.